Management accounting system, information quality and organizational performance: evidence from Libya / Naser Ghanem and Suzana Sulaiman - Ghanem, Naser; Sulaiman, Suzana (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
The purpose of this study is to examine the extent to which management accounting system (MAS) success, which is defined in terms of MAS effectiveness and system end user satisfaction, exerts an intervening effect on the relationship between information quality (IQ) and organisational performance (OP). A primary survey was conducted on a group of managers working in two different sectors in Libya. The two sectors are banks and petroleum companies. Results show that the usefulness of MAS is positively associated with IQ and mediates the indirect relation between IQ and OP. Specifically, end user satisfaction exerts a mediating effect on the relationship between IQ and OP. This study is limited to the effect of IQ as an independent variable on MAS effectiveness and OP in Libyan banks and petroleum organisations. The cross-sectional investigation presented in this study can establish association but not causality.